Newborns' clinical conditions are correlated with the neonatal assessment manual scorE (NAME) - Manzotti, Andrea; Cerritelli, Francesco; Lombardi, Erica; La Rocca, Simona; Biasi, Pamela; Chiera, Marco; Galli, Matteo; Lista, Gianluca (Frontiers in Pediatrics, 2022)
Objective: To investigate the relationship between the Neonatal Assessment Manual scorE (NAME) and newborns’ clinical condition on a large number of infants. The NAME model was developed as an instrument to assess the infant’s general conditions, especially in NICUs, by evaluating how the infant’s body responds to an external stressor such as static touch. Previous studies, employing experienced assessors, showed good validity indices as well as high inter-rater reliability. Study Design: Newborns were recruited at the “Vittore Buzzi” Paediatric Hospital NICU ward in Milan and their clinical conditions were collected through a standardized form – the complexity index. Two manual practitioners assessed all eligible newborns using the NAME scores. Data was analyzed using Kendall’s 𝛕 correlation and odds ratio (OR) to assess the relationship between the NAME scores and the complexity index. Results: 202 newborns (46% female; 34.1w ± 4.3; birth weight of 2,093.4gr ± 879.8) entered the study. The Kendall’s correlation between the clinical conditions (complexity index) and the NAME score was -0.206 [95% CI: (-0.292, -0.116), p-value <0.001], corresponding to an OR of 0.838 [95% CI: (0.757, 0.924), p-value <0.001]. Further exploratory analyses showed significant correlation between gestational age, birth weight and NAME scores. Conclusion: The present paper adds evidence to the NAME model validity by demonstrating its applicability in the clinical neonatological context.